Water-bearing characteristics and their influences on the reservoir capacity in terrestrial shale reservoirs: A case study of the lower Jurassic Ziliujing Formation in the Northeast Sichuan Basin, China. (January 2021) - Zhu, Deyu; Jiang, Zhenxue; Jiang, Shu; Yang, Wei; Song, Yan; Gao, Zhiye; Jiang, Tao; Cao, Xiangni; Li, Weibang; Zhang, Ye
Abstract: The water content in shale reservoirs has a negative effect on reservoir space capacity. Compared with marine shale, terrestrial shale is characterized by higher clay content and lower total organic carbon (TOC), which is more sensitive to water and decreases gas storage capacity. However, it is still not fully understood how water is distributed in nanopores and how shale reservoir capacity is significantly weakened. In this study, a series of measurements were conducted methodically, including a moisture-equilibrated experiment, high-pressure mercury injection, gas adsorption, air-liquid contact angle, spontaneous imbibition and nuclear magnetic resonance, to investigate the water-bearing characteristics and effects of lacustrine shale. On the macroscopic scale, it was confirmed that clay shale displays the strongest water adsorption capacity and holds 2–3 times more water than siliceous shale. Clay minerals, especially montmorillonite, adsorb approximately 4 times more water than shale and 20 times more water than kerogen at a relative humidity (RH) of 98%. Meanwhile, clay shale with high TOC adsorbed less water. At the microscopic scale, the pore structure parameters of pore volume (PV) and specific surface area (SSA) can decrease up to 1/2 and 1/3, respectively, which based on our terrestrial shale samples at the RH of 98%. Furthermore, PV declines with increasing RH, primarily between 2.5 nm and 80 nm, while SSA also declines and fluctuates from 2.5 nm to 20 nm with increasing RH, which suggests that SSA is more susceptible to water than PV. When the RH increases from 0% to 98%, the minimum critical aperture (DCAmin ) of the pore size shows an obvious shift from 2.5 nm to 7.5 nm, indicating that some nanopores are gradually damaged by water vapor and are unavailable for gas storage. In addition, water saturation in shale reservoirs maintains dynamic changes with thermal evolution. Finally, we proposed a multifactor controlled dynamic model and discussed the gas storage capacity of shale reservoirs with residual water. This study provides systematic and deep insight into water-bearing shale and is helpful for evaluating gas storage capacity in terrestrial reservoirs. Highlights: Water-bearing characteristics of terrestrial shale lithofacies are quite different. Total organic carbon, clay, and thermal evolution stage affect water content. Specific surface area is more susceptible to water than pore volume. A multi-factor controlled dynamic model of water distribution is established.